Kemampuan Penyuluh Agama Islam Non PNS Di Kabupaten Sumba Tengah dalam Menerapkan Teknik Komunikasi - Kibtiyah, Muhimatul (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to analyze the ability of non-civil servant religious counselors in Central Sumba Regency in applying communication techniques. This research uses a qualitative approach. The data source in this study is the head of the KUA and Islamic religious counselors and fostered citizens. Data collection techniques are done by observation, interview and document analysis techniques. The results of the study stated that (1) the understanding of religious instructors about good communication techniques was not yet maximal (2) the ability of religious instructors to implement informative communication techniques was already good (3) the ability of religious instructors to implement persuasive communication techniques was quite good (4) the ability of religious instructors in applying coercive communication techniques is not optimal.